THE EFFECTIVENESS OF GENERATING INTERACTION BETWEEN SCEMATA AND TEXT (GIST) TO TEACH WRITING VIEWED FROM STUDENTS’ INTELLIGENCE - Nuri Ati Ningsih (English Teaching Journal : A Journal of English Literature, Language and Education, 2013)
The  research  method  was  quasi  experimental  research  by  using  simple  factorial design  2x2.  The  population  in  this  research  was  the  second  grade  students  of  English Teaching Department of IKIP PGRI Madiun. The writer used cluster random sampling to get the sample. It consists of 60 students which were divided into two classes, II D consisting 30 students as a control class and II B consisting 30 students as an experimental class. The instruments  used to  collect  the data were  writing test  to  get  the score  of writing skill. Documentation was used to get the data of students’   intelligence. Before the instruments were used, the tryout was done to know the validity and readiability of instruments. The writer analyzed the data in term of their frequency distribution, normality, and homogeneity. Then,  the  data  were  analyzed  by  using  multifactoral  analysis  2X2.The  findings  in  this research lead to some conclusions: (1) GIST is more effective than DI for teaching writing; (2) The students having high intelligence have better writing skill than the students having low intelligence; and (3) There is an  interaction between teaching strategies and students’ intelligence for teaching writing. The effect of teaching strategies on the students’writing skill depends on the students’intelligence.